Gender-specific violence and/or abuse: strategy for dealing with a hidden phenomenon. (30th September 2020) - Dei, S; Marchetti, C; Monti, G; Pifferi, A; Moscatelli, C; Pagliara, C; Erba, F; Michelangeli, L; Lelli, S; Doretti, V
Abstract: Background: Exposing episodes of violence against women or hate crimes was extremely difficult in the past, due to a lack of awareness in emergency departments, the absence of a social, institutional and health network, and poor communication by Anti-Violence Centers. Until about 10 years ago, professional skills employed to address this kind of episodes were strictly related to the specificity of the trauma reported (gynecological, orthopedic, surgical and psychiatric). Purpose: introduce a necessary holistic approach, that takes into account all aspects of the issue that normally are completely overlooked. Methods: The "Codice Rosa" project began in the Grosseto Health Department (Tuscany) on 2009. It ensured reserved access to the emergency room for victims of violence, in particular women, children and discriminated persons. Later, it evolved into a regional network for women who have suffered from gender-based violence and for victims of hate crime violence. The project currently includes all victims, no matter whether they access the sanitary service through the emergency room, ambulatory or ordinary hospitalization. It follows a precise alert procedure triggering subsequent steps over the territory, with the goal to ensure ongoing support and a global care scheme. Results: from 2010 up to July 2019 in the Grosseto Health Department 3483 "Codice Rosa" (mistreatment, abuse, stalking) have been admitted, 3088 adults and 395 minors respectively. In Tuscany from 2012 up to July 2019, the Codice Rosa patients were 20162, 17305 adults and 2857 minors respectively. Conclusions: The program operates synergistically with other entities, institutions and overall with the local network of Anti-Violence Centers and Social Services, in line with national and international directives. It has provided a strong contribution to the development of current national guidelines in Italy. Key messages: Gender specific violence and hate crimes phenomenon have to be specifically addressed. Improving the regional/national networks among the various actors involved in the fight against gender violence and hate crimes.